2006
DOI: 10.1016/j.ecolecon.2005.11.011
|View full text |Cite
|
Sign up to set email alerts
|

The income–environment relationship: Evidence from a binary response model

Abstract: The empirical environmental Kuznets curve (EKC) literature is vast but far from conclusive.Many authors have analysed the existence of an EKC for various pollutants. Others have used the EKC framework to identify country characteristics that help to explain the incomeenvironment relationship. In this framework environmental degradation is analysed using a second or third order polynomial in income and a limited number of control variables.Some authors question whether this standard framework is appropriate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 37 publications
(50 reference statements)
2
10
0
Order By: Relevance
“…The strategy has the further advantage of avoiding the modelling of time‐series dynamics. The approach shares similarities with that of Verbeke and De Clercq (2006), whose primary specification uses a dependent variable equal to 1 for 5‐year periods in which income growth and reductions in sulphur emissions are simultaneously achieved, and 0 otherwise. The approach here focuses on the long‐run relationship between emissions and the explanatory variables rather than the reduced‐form relationship between income and emissions over 5‐year periods.…”
Section: Estimation Approach and Datamentioning
confidence: 99%
“…The strategy has the further advantage of avoiding the modelling of time‐series dynamics. The approach shares similarities with that of Verbeke and De Clercq (2006), whose primary specification uses a dependent variable equal to 1 for 5‐year periods in which income growth and reductions in sulphur emissions are simultaneously achieved, and 0 otherwise. The approach here focuses on the long‐run relationship between emissions and the explanatory variables rather than the reduced‐form relationship between income and emissions over 5‐year periods.…”
Section: Estimation Approach and Datamentioning
confidence: 99%
“…Roberts and Grimes (1997) found there is an inverted U-shaped relationship between CO 2 emission intensity and economic growth [4]. Dinda (2005) and Verbeke (2006) examined the homogeneity of the EKC hypothesis [5,6]. Meanwhile, studies (M, Wagner, 2008) on the EKC heterogeneity of different regions and different pollutants were conducted [7].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Different scholars hold different opinions about the environmental Kuznets curve hypothesis; some support the inverted U-shaped curve, while other studies show that it is U-shaped, N-shaped, monotonously rising and monotonously decreasing. Verbeke and Managi used empirical analysis to test the environmental Kuznets curve, and results showed that the EKC changing trajectory exists in most countries (Verbeke, 2006;Managi, 2006) …”
Section: Introductionmentioning
confidence: 99%